Effect of Cognitive Restructuring to Increase Students' Academic Resiliense - Durrotunnisa; Olga Maria Magdalena (Department of Guidance and Counseling, FIP, Undiksha, 2022)
The main problem in this research is the low academic resilience of students, which is characterized by difficulties in self-adjustment when studying during a pandemic. This study aims to improve students' academic resilience through group counseling services with cognitive restructuring techniques. This type of research is a quasi-experimental one group pre-test post-test design. This research was conducted four times with the number of research subjects 8 students. The instrument in this study used an academic resilience scale. Data were processed and analyzed descriptively and inferentially using the Wilcoxon sign rank test formula. The results of descriptive analysis show that before participating in group counseling services cognitive restructuring techniques of the 8 students studied, there were 6 students who had low academic resilience and 2 students who had moderate academic resilience. After participating in group counseling services, cognitive restructuring techniques have increased, namely 6 students who have high academic resilience and 2 students have moderate academic resilience. The results of inferential analysis show that there is a significant difference in students' academic resilience between before and after being given group counseling services using cognitive restructuring techniques. The effect of cognitive restructuring technique group counseling on students' academic resilience. The implication of the research is that resilience can be developed in counselees by applying all the stages of counseling that have been determined, starting from recognizing the problem, changing negative thoughts to a more positive direction as a solution to the problems faced.